Language acquisition process: implications for teaching English as a second language for sustainable development (2020)
This paper examines the process of language acquisition and its implications for teaching English as a Second Language in the effort to achieve the sustainable development goals. It further argues that effective teaching of English as a Second Language should be learnen-centred, innovative and highly interactive. Also, English Language teachers should model the right content, structure the process of instruction and involve learners in the teaching/learning process to facilitate second language acquisition in a multilingual country like Nigeria. The paper concludes by making recommendations on how to improve English language pedagogy.